PENGARUH KUALITAS AUDIT, AUDIT FEE, DAN PROFIL KANTOR AKUNTAN PUBLIK TERHADAP INDEPENDENSI AUDITOR - Waluyo, Anang Didik; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to analyze the influence of audit quality, audit fee, and Public Accountant Office (KAP) profile to the independency of auditor. The result of the analysis which has been done shows that: (1) the audit quality has significant influence to the independency of auditor; it indicates that the independency of auditor can be achieved if the auditor has good audit quality. When the audit quality level which is owned by the auditor is getting better, the independency of auditor is getting better as well, (2) audit fee has significant influence to the independency of auditor, it means that when the audit fee level which is owned by the auditor increase, the independency of auditor increase as well, (3) the Public Accountant Office (KAP) profile has significant influence to the independency of auditor, it shows that when the Public Accountant Office (KAP) profile is getting larger, the independency level which is owned by the auditors is getting larger as well.Keywords: corporate governance, institutional ownership, managerial ownership, audit committee, firm value.